Analysis of the failure mechanisms of the basilica of Santa Maria di Collemaggio during 2009 L'Aquila earthquake. (15th September 2015) - Arcidiacono, Vincenzo; Cimellaro, Gian Paolo; Ochsendorf, John A.
Highlights: Cause of the failure of the basilica of Santa Maria di Collemaggio during the 2009 L'Aquila earthquake. Comparison of analytical and numerical models to explain the failure of the transept columns. The seismic performance of the façade and the role of previous strengthening during 2009 earthquake. Different modelling approaches to explain the seismic behaviour of the historic masonry structure. Abstract: In the paper are presented and compared different analytical and numerical models to explain the failure of the transept columns, which led to the collapse of the central dome of the 13th century basilica of Santa Maria di Collemaggio during the 2009 L'Aquila earthquake. The three models have been used to analyse respectively the horizontal performance of the church ( Beam model ), the vertical performance of the transept ( Vertical model ) and the residual capacity of the façade ( Soil–Brick model ). Results show that the collapse of the transept columns due to axial load is unlikely, while the collapse due to the global torsional behaviour of the church is more probable as already indicated by the authors elsewhere. Furthermore, numerical results have also shown that the frontal façade, without the temporary scaffolding system, would have not been able to withstand seismic events such as the 2009 L'Aquila earthquake.